2020
DOI: 10.1101/2020.06.10.144188
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Age-dependent progression of SARS-CoV-2 infection in Syrian hamsters

Abstract: 22In late 2019, an outbreak of a severe respiratory disease caused by an emerging 23 coronavirus, SARS-CoV-2, resulted in high morbidity and mortality in infected humans 1 . 24Complete understanding of COVID-19, the multi-faceted disease caused by SARS-CoV-25 2, requires suitable small animal models, as does the development and evaluation of 26 vaccines and antivirals 2 . Because age-dependent differences of COVID-19 were identified 27 in humans 3 , we compared the course of SARS-CoV-2 infection in young and a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
88
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 78 publications
(99 citation statements)
references
References 30 publications
11
88
0
Order By: Relevance
“…COVID-19 is less frequently reported in children than in adults and elderly people (27)]. Two studies in hamsters (12,13) reported more severe lesions and clinical signs in older animals. The oldest ferrets used in experimental studies were 20 month old (8)(9)(10)(11)], therefore no conclusion can be drawn on the effect of age in this species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…COVID-19 is less frequently reported in children than in adults and elderly people (27)]. Two studies in hamsters (12,13) reported more severe lesions and clinical signs in older animals. The oldest ferrets used in experimental studies were 20 month old (8)(9)(10)(11)], therefore no conclusion can be drawn on the effect of age in this species.…”
Section: Discussionmentioning
confidence: 99%
“…To fight COVID-19, neither vaccines nor therapeutic treatments are currently available. Understanding the pathogenesis of the SARS-CoV-2 infection is key to maximize prevention and to develop therapeutic solutions, and this is possible through susceptible animal models such as non-human primates (cynomolgus (Macacca fascicularis) and rhesus (Macacca mulatta) macaques), cats, hamsters and ferrets (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)], being the two latest species the most economic and easiest to house and handle. To our knowledge, all ferrets and hamsters experimental infection studies (9,13),] published so far, apart from two studies (9,13),] were performed with high doses of SARS-CoV-2 (ranging from 8.10 4 TCID50 to 10 5.5 TCID50 or 10 6 pfu per animal), independently of animal weight and mainly with the objective of inducing severe infections.…”
Section: Introductionmentioning
confidence: 99%
“…Of particular interest is the fact that SARS-CoV-2 infection in hamsters reflect some of the demographic differences of COVID-19 in humans. Thus, aged hamsters as well as male hamsters seem to develop a more severe disease than young and female hamsters respectively 37,38 .…”
Section: Syrian Hamster Modelmentioning
confidence: 92%
“…By 5 dpi, a patchy, largely interstitial pneumonia was present with onset of repair and regeneration, followed by almost complete recovery at 14 dpi. Other determinants include the age of the animals (13) and infectious dose used (10).…”
Section: To the Editormentioning
confidence: 99%